Teaching and learning argumentative writing in high school English language arts classrooms - Newell, George (George Edward) 1951-; Bloome, David; Hirvela, Alan; Lin, Tzu-Jung; VanDerHeide, Jennifer; Olsen, Allison Wynhoff; Buescher, Eilleen; Goff, Brent; Kim, Min-Young; Ryu, SangHee; Weyand, Larkin (Routledge, 2015)
Focused on the teaching and learning of argumentative writing in grades 9-12, this important contribution to literacy education research and classroom practice offers a new perspective, a set of principled practices, and case studies of excellent teaching. The case studies illustrate teaching and learning argumentative writing as the construction of knowledge and new understandings about experiences, ideas, and texts. Six themes key to teaching argumentative writing as a thoughtful, multi-leveled practice for deep learning and expression are presented: teaching and learning argumentative writing as social practice, teachers' epistemologicai beliefs about argumentative writing, variations in instructional chains, instructional conversations in support of argumentative writing as deep learning and appreciation of multiple perspectives, contextualized analysis of argumentative writing, and the teaching and learning of argumentative writing and the construction of rationalities -- Book jacket.